Laser heating applications : analytical modelling - Yilbas, B. S. (Elsevier Science, 2012)
Thermal treatment of materials occupies a significant, increasing proportion of MSE activity and is an integral component of modern curricula as well as a highly monetized component of industrial production. Laser processing of materials offers advantages over conventional methods of processing. Some of these advantages include fast processing, precision of operation, low cost and local treatment. Analytical modelling of laser processing gives insight into the physical and mathematical aspects of the problem and provides useful information on process optimization. However the important physi.